Gallium(III) Corrole Complexes as Near‐Infrared Emitter – Synthesis, Computational and Photophysical Study. Issue 10 (16th February 2021) - Haas, Michael; Krisch, Dominik; Gonglach, Sabrina; Bechmann, Matthias; Scharber, Markus C.; Ertl, Martin; Monkowius, Uwe; Schöfberger, Wolfgang
Abstract: We report on the chemical synthesis and characterization of free‐base A2 B‐ and A3 ‐ meso ‐TIPS ethynyl corroles, which serve as a precursor for metalation with gallium(III)chloride and subsequent in‐situ sila Sonogashira cross‐coupling reaction. Under ambient conditions and with a common catalyst system the reaction with different aryliodides proved to be successful. Compared to the well‐known Ga(III)‐pyr‐5, 10, 15‐trispentafluorophenylcorrole complex, the emission wavelengths of such gallium(III) corroles complexes could be shifted bathochromically by up to ∼3100 cm −1 to the near‐infrared region (NIR). The described synthetic procedure establishes a facile way to obtain organic near‐infrared‐emitters based on gallium(III) meso ‐aryl‐ethynyl corrole complexes. Abstract : We herein report the synthesis of free‐base and gallium A2 B‐/A3 ‐ meso ‐ethynyl corroles and subsequently, show the synthesis of novel gallium(III) A2 B‐ and A3 ‐ meso ‐arylethynyl corrole complexes. Theoretical and photophysical studies reveal that the optical properties of such gallium(III)‐ethynylcorroles can be selectively tuned with different aryl‐substituents.